Effect of Wordwall-Assisted Numbered Heads Together on Junior High School Students’ Mathematical Conceptual Understanding - Elviza Dwi Wahyuni; Kasman Ediputra; Adityawarman Hidayat (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Students’ mathematical conceptual understanding remains an important concern in junior high school mathematics learning. Inadequate conceptual understanding may lead to students’ difficulties in connecting mathematical concepts and solving mathematical problems. Learning that involves collaboration and the use of interactive media is considered capable of promoting students’ active engagement. This study aims to examine the effect of the Wordwall-assisted Numbered Heads Together (NHT) learning model on students’ mathematical conceptual understanding of exponents. This study employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The research subjects were Grade VIII junior high school students consisting of an experimental class and a control class. The research instrument was a mathematical conceptual understanding test developed based on four indicators: restating concepts, classifying objects, representing concepts in various forms, and applying concepts in problem solving. The data were analyzed using an independent samples t-test. The results showed a significant difference between the mathematical conceptual understanding of students taught using the Wordwall-assisted NHT model and those taught using conventional instruction. The Wordwall-assisted NHT model had a positive effect on improving students’ mathematical conceptual understanding, as indicated by the higher posttest mean score of the experimental class (62.08) compared with the control class (51.68), with a Sig. (2-tailed) value of 0.017 < 0.05. These findings indicate that cooperative learning supported by interactive media can serve as a strategic alternative for improving the quality of junior high school mathematics learning.